Meninjau strategi manajemen operasional pada jasa perhotelan pasca pandemi COVID-19 di Bangil - Putri, Evi Saskia (Maliki Interdisciplinary Journal, 2023)
In the midst of crises such as the COVID-19 pandemic, the importance of management strategies in the hospitality sector is increasing. To describe common management strategy practices in the hospitality sector, we conducted a systematic review of the literature. We analyzed 48 articles published between 2020 and 2021 from the Web of Science (WoS) Database, covering the period before and during the pandemic. In our review, it is seen that strategic management practices in the hospitality sector have evolved over the years. However, there is some conceptual overlap and empirical findings between sustainable practices applied in the hospitality sector. Research on sustainable practices in the hospitality sector is also limited to certain contexts. In addition, the deficiencies in the research involve the supporting factors, the results from the practice, and the integration of theory in the studies. By following the guidelines outlined in this review, it is hoped that research on strategic management practices can continue to grow and provide valuable insights in the post-COVID-19 pandemic years. This research is one of the few studies that systematically analyzes the practice of management strategies in the hospitality sector before and during the COVID-19 pandemic. We conclude this review by presenting a comprehensive research agenda and a framework for guiding future theoretical and empirical developments in this field.